Comparing the levels of expectation and satisfaction of Indian and foreign adventure tourists visiting India - Lather, Anu Singh (Applied Studies in Agribusiness and Commerce, 2012)
Purpose – The present study is undertaken to explore the difference between expectation and satisfaction level of Indian and foreign adventure tourists and the relationship between the levels of expectation and satisfaction of Indian and foreign adventure tourists.Methodology – The data has been gathered from a sample of 300 adventure tourists comprising of 150 Indians and 150 foreigners. A principal component analysis with varimax rotation has identified 28 relevant items, which are broadly clustered into 6 significant factors. They are labeled as Aesthetic Appeal, Facilities, Accommodation, Information, Food and Safety and Security.Findings – The findings of this study revealed significant differences between the levels of expectation and satisfaction of adventure tourists of Indian and foreign origin. The level of expectation among the Indian and foreign adventure tourist is higher and, comparatively, the level of satisfaction is lower. The level of expectation and the level of satisfaction of Indian adventure tourists are positively and significantly correlated with respect to variables such as Aesthetic Appeal, Facilities, Safety and Security and Accommodation. For the foreign adventure tourist, the level of expectation and level of satisfaction are positively and significantly correlated with respect to variables such as Information, Aesthetic Appeal, Facilities and Food.Practical Implications – The research findings will help in the promotion of adventure tourism in India.Originality/ Value – The identified factors can be used for similar kinds of studies at different destinations. The results of the study would be instrumental in developing strategies for ensuring more satisfied tourists.